الأحكام المتعلقة بالإصبع الزائدة من منظور الفقه الإسلامي - أحمد، أحمد عطا الله عبدالباسط Ahmed, Ahmed Atallah Abdulbaset (جامعة الأزهر - كلية الشريعة والقانون بأسيوط, 2018)
الحمد لله رب العالمين والصلاة والسلام على أفضل الأنبياء وخاتم المرسلين سيدنا محمد وعلى آله وصحبه والتابعين لهم بإحسان إلى يوم الدين، أما بعد،،، فقد تناولت هذه الدراسة قضية من القضايا الطبية المعاصرة ألا وهي الإصبع الزائدة من حيث تعريفها وبيان أسبابها وأثرها على الأفراد والأحكام الفقهية المتعلقة بها. الإصبع الزائدة هي عبارة عن تشوه خلقي يؤدي إلى زيادة في عدد أصابع اليدين والقدمين عن العدد الطبيعي. وهناك الكثير من الأسباب لزيادة الأصابع فقد يكون التعرض لمواد كيماوية وقد يكون نتيجة خلل في جينات الحيوان المنوي الذي لقح البويضة، وذلك في شكله وحجمه أو في عدد كروموسوماته أو تكون البيضة نفسها هي حاملة للخلل أو كليهما. يوجد ارتباط وثيق بين التشوه الخلقي في الشكل الخارجية للجسم، وبين الحالة الصحية والنفسية لصاحبها وأسرته، فتصور الشخص لقبح منظره الخارجي بخروجه عن الشكل المألوف وانشغاله بذلك يؤدي إلى ظهور أعراض نفسية إكلينيكية باتت ثابتة من خلال التجربة والمشاهدة، واضطراب سلوكي يتمثل في العزلة الاجتماعية، وسوء الأداء المهني. عند الوضوء يجب غسل الإصبع الزائدة غير المتميزة عن الأصلية بنحو فحش قصر وضعف بطش، أما الإصبع الزائدة المتميزة فإن كانت بمحل الفرض فيجب غسلها، وإلا لم يجب. ينتقض الوضوء حال مس الذكر بإصبع زائدة سواء كان به إحساس أو لا شريطة كون المس بدون حائل وكونه مسا بشهوة. الإصبع الزائدة في العبد والأمة عيب يثبت الخيار للمشتري بين رد المبيع وبين إسماكه وأخذ الأرش. وفي باب الجنايات تؤخذ الإصبع الزائدة من الجاني قصاصا بالإصبع الزائدة من المجني عليه إذا توافرت في الجناية شروط القصاص فيما دون النفس. إذا كانت الإصبع الزائدة على هيئة وخلقة الأصابع الأصلية ويتصرف بها كالأصلية ففي هذه الحالة تؤخذ الإصبع الاصلية قصاصاً بالإصبع الزائدة وإلا فلا. لا تؤخذ الإصبع الزائدة قصاصا بالإصبع الأصلية. وجوب عشر الدية في الإصبع الزائدة المساوية للأصابع الأصلية في القوة والتصرف، ولو قطعت مع الكف. تجوز إزالة الإصبع الزائدة ولكن ليس جوازا مطلقا ولكنه مقيد بما إذا كانت الإصبع الزائدة على غير هيئة الأصابع الأصلية، أو كانت على هيئة الأصابع الأصلية ولكنها تؤلم صاحبها وتؤذيه. وآخر دعوانا أن الحمد لله رب العالمين. وصل اللهم وسلم وبارك على سيدنا محمد وعلى آله وصحبه والتابعين.
Praise be to Allah, the Lord of the Worlds, and prayers and peace be upon the best prophets and the Seal of Messengers Muhammad, his family and companions, and those who follow them with charity to the Day of Judgment. ,,, After This study dealt with the issue of contemporary medical issues, namely the extra finger in terms of definition and the reasons for the impact and impact on individuals and jurisprudence related to them. The extra finger is a congenital malformation that increases the number of fingers and toes from the normal number. There are many reasons to increase the fingers may be exposure to chemicals and may be a result of defect in the genes of the sperm that oozed the egg, in form and size or in the number of chromosomes or the egg itself is the carrier of the defect or both. There is a close link between congenital deformity in the external appearance of the body, and between the health and psychological state of the owner and his family. The person conceives of the ugliness of his external appearance by leaving the familiar form and his preoccupation with this leads to the emergence of psychological psychological symptoms that have become constant through experience and observation. Professional performance. When doing wudoo ', the extra finger, which is not distinguished from the original, should be washed with a small, weak, and weak jaw. The extra finger should be washed, otherwise it should not be washed. Wudoo 'is invalidated if he touches the male with an excess finger, whether it is felt or not, provided that the touching is without a barrier and that it is tantamount to lust. The excess finger in the slave and the nation is a defect that proves the buyer's choice between the return of the sale and the holding of the land. In the case of crimes, the extra finger of the offender is taken with an excess finger from the victim if the conditions of retribution are available in the crime, without the soul. If the extra finger on the body and the creation of the original fingers and behaves as the original in this case the original finger is taken with an extra finger bite or else not. Do not take the extra finger with the original finger. Obligation of ten dirhams in the finger of excess equal to the original fingers in the force and act, even cut with the palm. The extra finger may be removed, but it is not an absolute passport, but it is restricted whether the finger is on the other side of the original fingers, or is in the shape of the original fingers, but it hurts the owner and harms him. And Praise be to Allah, the Lord of the Worlds Peace, blessings and blessings be upon our master Muhammad and his family and companions.
Keywords: الفقة الاسلامى -- أطراف الجسم -- الأصابع الزائدة -- الأحكام الفقهية